Practices and perceptions of strength and conditioning in female golf: A survey study of touring professionals - Robinson, L.; Murray, A.; Mountjoy, M.; Scott, F.; Glover, D.; Coughlan, D.; Turner, A.; Bishop, C. (International Journal of Sports Science & Coaching, 2024)
The aim of the study was to provide an understanding of current practices and perceptions of strength and conditioning (S&C) training in female touring professionals. A cross-sectional, explorative survey was undertaken and contained 30 questions separated into four sections: (i) general participant information, (ii) S&C practices, (iii) Likert scale questions on S&C for golf performance, and (iv) knowledge and awareness of S&C. A total of 102 players completed the survey with a combination of multiple-choice questions (MCQs), open-ended questions, and Likert scale style questions utilised throughout. Results showed that =94% of players believed that strength and power in both the lower and upper body, in addition to flexibility, were the most important physical characteristics to complement golf shot metrics (e.g. clubhead speed [CHS], ball speed, carry distance, etc.). However, 26% of players conducted S&C training only in the off-season, with 21% suggesting that they had a fear of injury from S&C training. When considering the barriers to undertaking S&C training, the most common reasons included time constraints (20%) and players wanting to prioritise golf practice (15%). Finally, 58% of players believed that training in the weight room should replicate the golf swing. Although it is positive to see that the main physical characteristics for golf are well-understood by professional players, it is also evident that further education and knowledge translation is required relating to the application of S&C training for performance enhancement and injury risk mitigation purposes.